2020
DOI: 10.1021/acsami.0c06872
|View full text |Cite
|
Sign up to set email alerts
|

Small Morph Nanoparticles for Deep Tumor Penetration via Caveolae-Mediated Transcytosis

Abstract: The tumor penetration of nanomedicines constitutes a great challenge in the treatment of solid tumors, leading to the highly compromised therapeutic efficacy of nanomedicines. Here, we developed small morph nanoparticles (PDMA) by modifying polyamidoamine (PAMAM) dendrimers with dimethylmaleic anhydride (DMA). PDMA achieved deep tumor penetration via an active, energy-dependent, caveolae-mediated transcytosis, which circumvented the obstacles in the process of deep penetration. PDMA remained negatively charged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Besides enhanced tumor accumulation, potent drug delivery also relies on deep tumor penetration. , B16F10 tumor spheroids were employed as a three-dimensional (3D) model to mimic the tumor tissues in vitro to preliminarily evaluate the penetration capability of PPN. Tumor spheroids were visualized using a CLSM with Z -stack scanning after treatment with Cou 6-loaded PPN with/without laser irradiation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Besides enhanced tumor accumulation, potent drug delivery also relies on deep tumor penetration. , B16F10 tumor spheroids were employed as a three-dimensional (3D) model to mimic the tumor tissues in vitro to preliminarily evaluate the penetration capability of PPN. Tumor spheroids were visualized using a CLSM with Z -stack scanning after treatment with Cou 6-loaded PPN with/without laser irradiation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Mitochondrial-targeting drug carriers should not only shield the positive charge of CTPP but should also successfully escape from the trapping of endosomes/secondary lysosomes. Recent reports have revealed that the positively charged nanoparticles could be rapidly internalized via caveolae-mediated endocytosis and then by vesicle-mediated transcytosis [ 34 , 35 ]. This transcytosis process might explain why CTPP-containing nanoparticles have low mitochondrial-targeting efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…3D tumor spheroids of B16 cells were prepared by hanging drop method according to literature reports. [ 32 ] In brief, 20 µL of the 0.24% methylcellulose culture medium solution containing 3000 cells were transferred onto the lid of 24‐well culture plates and were inverted over culture plate. These cells were incubated for one week.…”
Section: Methodsmentioning
confidence: 99%